Dampak Pelaksanaan Pelatihan Mitigasi Bencana oleh BPBD DKI Jakarta bagi Masyarakat Kelurahan Cawang, Jakarta Timur - Nur Izzati, Aulia (Universitas Negeri Surabaya, 2023)
This study aims to describe the implementation and impact from disaster mitigation training by Badan Penanggulangan Bencana Daerah (BPBD) DKI Jakarta. The research was conducted in June - October 2022. This research method is descriptive qualitative. The research subjects consisted of key informants, namely the Community Empowerment Sub-Coordinate Disaster Analyst and the Head of the Cawang Village Government Section and three participants as supporting informants. Data collection techniques used are observation, interviews, and literature studies. Data analysis techniques in this study used descriptive analysis, including reduction, presentation, and conclusions. The results of the study show that the main objective of the training is to form a community synergy that is resilient to disasters through understanding, applying, and disseminating the knowledge. The impact of the training is evidenced by the statements of the participants who felt there was a change in knowledge regarding first aid techniques and disaster evacuation.